Pendampingan guru dan Pengembangan Soal Matematika Berkarakter Olimpiade tingkat SMA - Palupi Sri Wijayanti (Celebes Abdimas: Jurnal Pengabdian Kepada Masyarakat, 2020)
This devotion aims to provide mathematics teachers assistance in developing Olympic characters at the high school level. The devotional activities are coordinated with the math teacher and test the question to the students. The results showed that all participants stated that this devotional activity helped them enrich knowledge and insights related to the mathematical Olympics. As a form of evaluation, participants can independently develop the questions that have been prepared so that all students can use it with very diverse student characteristics. The accompanying participants' assessment obtained a statement that mentioned that the service team's material according to the math teacher's needs related to the character of the math Olympic problem.